2010
DOI: 10.3109/09553002.2010.518200
|View full text |Cite
|
Sign up to set email alerts
|

Daily exposure to inhomogeneous static magnetic field significantly reduces blood glucose level in diabetic mice

Abstract: Daily SMF exposure repeated for several weeks is protective against the development of high blood glucose level in diabetic mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…For mice with type 2 diabetes, glucose was significantly reduced (p<0.01) only for mice treated with 600 mT. A similar reduction trend for the resting blood glucose of STZ-induced diabetic mice was reported for mice housed in cages and exposed to nonhomogeneous fields for 30 minutes/day for six weeks [ 35 ]. The SMF-treated diabetic mice were exposed to about 477 mT at their feet and about 2.8 mT at the top of their heads.…”
Section: Reviewsupporting
confidence: 73%
“…For mice with type 2 diabetes, glucose was significantly reduced (p<0.01) only for mice treated with 600 mT. A similar reduction trend for the resting blood glucose of STZ-induced diabetic mice was reported for mice housed in cages and exposed to nonhomogeneous fields for 30 minutes/day for six weeks [ 35 ]. The SMF-treated diabetic mice were exposed to about 477 mT at their feet and about 2.8 mT at the top of their heads.…”
Section: Reviewsupporting
confidence: 73%
“…If in vitro evidence was found on the SMF-exposure induced inhibition or assistance of the release of pro- and anti-inflammatory cytokines, a possible background mechanism of in vivo experienced antinociceptive effects in invertebrates [18], in mice [19][25], and in humans [26] would be supported. Therefore, the present set of in vitro experiments was designed to prove the null-hypotheses that exposure of PBMC to an inhomogeneous SMF for up to 24 h leads to a significant change in the:…”
Section: Introductionmentioning
confidence: 99%
“…For example, exposure to a static electric field (7 kV/m) combined with 3 mT SMF ( Carter et al, 2020 ) and downward SMF of 100 mT ( Yu et al, 2021 ) can have positive effects on T2D mice. Furthermore, exposure to 2.8–476.7 mT heterogenous SMFs for 12 weeks can significantly alleviate hyperglycemia in STZ-induced T1D mice ( László et al, 2011 ). These studies also showed that lower SMFs (<0.5 T) can decrease ROS levels, in contrast to our findings on high-gradient SMFs.…”
Section: Discussionmentioning
confidence: 99%